An elevated platform in front of the entrance of a Koli home - Mumbai Archive Project Team (Jio Institute, 2024)
An elevated platform in front of the entrance is a common design element in many Koli houses. People used this space for a variety of activities, such as socialising with neighbours and purchasing produce from mobile vendors.